The Fragile Chain: A Narrative Review of Communication Breakdown in Time-Sensitive Diagnoses Across the ED-Radiology-Inpatient Continuum - Alenizi, Sarah Farhan; Al-Mutairi, Fawzia Zayed Eid; Alabsi, Abidah Abed Obaidallah; Alotaibi, Yousef Saif W; Almarzoghi, Aljoharah Ghazi; Shehatah, Asmaa Anwar; Aldossari, Jamaan Bakheet Abdullah; Zaylaee, Nawal Yahya Ali; Alotaibi, Raed Ateeq Talmas; Alruweaili, Tirad Rakid Mushih; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: In time-sensitive medical conditions such as acute stroke, aortic dissection, and major trauma, diagnostic delays of minutes can drastically alter patient outcomes. The diagnostic pathway is a high-stakes relay involving multiple handoffs: from emergency department (ED) nursing and physicians, to radiographers, to radiologists, and finally to inpatient or interventional teams. Failures in communication at any point in this chain are a major source of preventable diagnostic error and patient harm. Aim: This narrative review aims to synthesize evidence on the critical communication pathways, vulnerabilities, and enabling strategies for handoffs from the ED through radiology to definitive inpatient care for time-sensitive diagnoses. Methods: A comprehensive literature search was conducted in PubMed, CINAHL, Scopus, and Web of Science (2010-2024). Results: The review identifies systemic vulnerabilities at each handoff: incomplete clinical information provided with imaging orders, ambiguous verbal communication, inefficient report dissemination, and failures in critical result notification. It highlights the pivotal but often overlooked roles of the radiographer as a situational communicator and the medical secretary as an information flow expediter. While health information systems like critical result alerts offer solutions, they often generate alert fatigue and can be circumvented. Conclusion: Safeguarding time-sensitive diagnoses requires a systems-engineering approach that hardwires communication protocols, formally recognizes the communicative roles of all team members (including radiographers and secretaries), and optimizes health information technology to support, not hinder, the cognitive and collaborative work of diagnosis.